Talent management perspectives in a South African provincial department - Saurombe, Musawenkosi Donia (Frontiers in Organizational Psychology, 2025)
IntroductionTalent management continues to evolve rapidly in various industries, due to factors such as constantly advancing technology, remote and hybrid working arrangements, and the consequently changing nature of work and expectations of both employers and employees. This research particularly aimed to understand the employee perspectives regarding talent management in a South African provincial Department.MethodsA mixed-method case study was employed, with an initial qualitative component and a subsequent quantitative component. A combination of manual and computer assisted qualitative data analysis techniques were used to thematically analyze the views of 14 participants, while the Statistical Package for Social Sciences was used to generate descriptive statistics depicting the views of the 135 respondents consulted in this research.ResultsTalent management practices and leadership approach to talent management were the two main themes developed from the qualitative research findings; where participants highlighted the importance of adopting practices which enable the maximization and continuous improvement of their human capital, supported by proactive and exemplary institutional leadership. The quantitative results revealed the current state of strategic talent management practices in the department, emphasizing various needs including a more inclusive workplace culture, enhanced employee work-life balance, as well as the skills development of current employees and future institutional leadership.DiscussionThe research results may enhance the implementation of effective talent management practices by leaders and human resource practitioners within the selected provincial Department and potentially offer related guidelines for those in the broader South African government context.